Professional Self-Development as a Psychological and Pedagogical Category - Valentyna Frytsiuk (Pedagogical Discourse, 2015)
The article is based on theoretical and empirical research analyzes the problem of professional self-development of future teachers. The author considered professional development and individual self-development as an object of research of psychologists and teachers;  she outlines the different methodological approaches to its consideration. This view of different scholars regarding interpretation of the terms «self-development», «professional self» with regard to various psychological, pedagogical and other approaches to understanding the nature of this phenomenon; interconnection outlines the concepts of «self-development», and «professional self-development». Displaying aspect to address the problem of teacher professional self-development position synergistic approach. It is concluded that professional self-development is related to a combination of internal structural components of the individual psyche aimed at its constructive interaction with the environment by getting personally meaningful and adequate requirements of society result profession. Defined as professional self conscious human activity aimed at complete fulfillment themselves as individuals in the social sphere, which determines its future profession. Attention is focused on the feasibility address of the problem of professional self-development through the prism of readiness for implementation.